Conditional Lending Under Altruism - Mourmouras, Alex (IMF Working Papers; Working Paper ;, 2004)
We analyze how the altruism of an international financial institution (IFI) towards its lowincome member countries (LICs) alters the effectiveness of its loans. We study IFI loans to a credit-constrained LIC. The IFI's repayment policy is determined by the interplay of its concerns for the welfare of the loan recipient and its fiduciary responsibilities to creditor countries. If the IFI is unable to commit to repayment terms in advance, conditional loans are superior to unconditional loans. Thus, IFI altruism and the inability to commit are sufficient reasons to equip loans with conditions. Conditional loans produce an efficient allocation of resources, so altruism is not a fundamental reason that loans fail to increase welfare.